Prevalence of pulmonary arterial hypertension in the Colombian Caribbean. (May 2019) - Miranda-Machado, Pablo; Baños-Alvarez, Ivan; Alvarez-Barrios, Alvaro
In Latin America, there are no specific data on the prevalence of pulmonary arterial hypertension (PAH). For this reason, the Registro Latinoamericano de Hipertensión Pulmonar (RELAHP) is under development. The aim of this study is to estimate the prevalence of PAH in the Colombian Caribbean in 2015 based on data from a private health insurance company (PHIC) with coverage in that region. All the Individual Service Delivery Registries (RIPS) of all ambulatory care centers that serve the population of the Colombian Caribbean region affiliated with a PHIC selected for this research were reviewed. All patients who had a diagnosis of pulmonary hypertension (PH) were included (International Classification Diseases 10-Revision [ICD-10 I270, I272, I278, and I279]). Subsequently, the information on electronic medical records was reviewed. To estimate the prevalence of PAH, the total population of the PHIC and population projections of Colombian Caribbean by Departamento Administrativo Nacional de Estadisticas (DANE) was used. We identified 27 patients with a confirmed diagnosis of PH and 18 patients with a confirmed diagnosis of PAH. Taking into account the total population affiliated to the Caribbean Regional of the PHIC selected for the study in September 2015, a PAH prevalence of approximately 28 cases per million inhabitants is estimated. The mean of age was 22 ± 21.4 years (14.8% children) and 17 (62.9%) were girls/women. The majority of patients presented with PAH (Group 1) (66.6%). The estimated number of cases of PH in Colombian Caribbean in 2015 is approximately 292 cases or 1 in 35, 760. Epidemiological estimates of PAH in the Colombian Caribbean are compatible with the definition of orphan or rare diseases. The majority of patients are female.